Ewolucja pojęcia celu małżeństwa - Kosowicz, Stanisław (Prawo Kanoniczne, 1988)
In the period between of old and new Codes the Canonical Law it followed the censure included in the 1013 § 1 Code Law of 1917 year. The development of the anthropological sciences contributed to call attention to man as the being sensual and spiritual. The thinkers upon the basis of the attainment of the study of mental diseases, psychology, phenomenology began to grasp the person from the psichological — personalical side. It produced the critique of the definition of the aim the marriage included in the Code. It reproached, the expression „the firstrate aim” — „the second-rate aim” are artificial and inacurate with reference to the marriage. The Popes standing up voice in theis question did support the learning in the Code. However the critique of these concepts conducted in the consequence, John Paul The Second promulgating the new Code Canonical Daw of 1983 year hat not used these terms to determine the aim of the marriage.